THE LEGAL ISSUES REGARDING THE USE OF ARTIFICIAL INTELLIGENCE TO SCREEN SOCIAL MEDIA PROFILES FOR THE HIRING OF PROSPECTIVE EMPLOYEES - Sershiv Reddy (Obiter, 2022)
The fourth industrial revolution has introduced advancement in technologies that have affected many commercial sectors in South Africa, and the employment sector is no exception. One of these advancements is the creation of artificial intelligence technologies that can assist humans to make everyday tasks quicker and more efficient. It has become common for organisations to screen social media profiles in order to gain information about a prospective employee. With the aid of artificial intelligence, employers can use such systems to easily sift through social media profiles and access the data it needs. Although these technological creations have many successful outcomes, artificial intelligence systems can also have drawbacks, such as inadvertently discriminating against certain groups of people when data is collected, processed and stored. Issues surrounding privacy breaches are also raised where artificial intelligent systems seek to access personal information from social media profiles. Prospective employees will need to be informed that their social media profiles are being screened and the artificial intelligence system needs to be programmed properly to ensure that data is correctly and fairly processed and collected.